2015
DOI: 10.1144/jgs2014-085
|View full text |Cite
|
Sign up to set email alerts
|

Magmatism, mantle evolution and geodynamics at the converging plate margins of Italy

Abstract: Abstract:The Plio-Quaternary magmatism in the Tyrrhenian Sea area exhibits wide compositional variations, which cover almost entirely those observed for volcanic rocks worldwide. Some volcanoes (Etna, Iblei, Sardinia, etc.) range from tholeiitic to Na-alkaline, and display elemental and isotope signatures typical of FOZO and EM-1 ocean-island basalts (OIB). Other volcanoes (Aeolian Arc, Italian peninsula) range from calc-alkaline-shoshonitic to K-alkaline, exhibit typical 'subduction-related' trace element sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 186 publications
(302 reference statements)
3
40
0
Order By: Relevance
“…These gaps match with major faults affecting the Apenninic wedge at the surface. They are observed in the 100 km depth slice but not documented at greater depth, and they define a slab structure consistent with the distribution of the main Plio‐Quaternary Apenninic magmatic provinces [ Peccerillo and Frezzotti , ]. Our tomography model also documents the along‐strike continuity of the Adriatic slab in the Northern Apennines, suggesting that the role of slab tearing in this latter area is possibly overestimated [e.g., Rosenbaum et al ., ].…”
Section: Discussionmentioning
confidence: 60%
“…These gaps match with major faults affecting the Apenninic wedge at the surface. They are observed in the 100 km depth slice but not documented at greater depth, and they define a slab structure consistent with the distribution of the main Plio‐Quaternary Apenninic magmatic provinces [ Peccerillo and Frezzotti , ]. Our tomography model also documents the along‐strike continuity of the Adriatic slab in the Northern Apennines, suggesting that the role of slab tearing in this latter area is possibly overestimated [e.g., Rosenbaum et al ., ].…”
Section: Discussionmentioning
confidence: 60%
“…Here the rather sharp posteriors translate into small errors in the estimation of the geothermal gradient in most of the locations ( σ <1 °C/km). Interestingly, we derive high thermal gradients, between 30 and 40 °C/km, for stations located in the Tuscan magmatic province where “orogenic” magmatism took place in the last 8.5 Ma, related to the westward subduction of the Adriatic plate and formation of the Apenninic orogen (Peccerillo & Frezzotti, ). The chemical signatures of both intrusive and extrusive magmatic products indicate heterogeneous mantle sources with the contamination of crustal melts and fractional crystallization within the crust.…”
Section: Discussionmentioning
confidence: 83%
“…We collected mafic samples on the islands of Alicudi, Filicudi, Salina, and Stromboli based on previous studies [e.g., Francalanci et al, 2013;Lucchi et al, 2013aLucchi et al, , 2013bLucchi et al, , 2013d] that suggested that the units collected are not only the most mafic but also they do not show any important evidence of crustal contamination. Peccerillo and Frezzotti [2015] demonstrated that samples with MgO 3.5 wt. % do not show significant evidence of crustal interaction in their incompatible elements ratios and radiogenic isotope signatures.…”
Section: Methodsmentioning
confidence: 99%